Statistical Channel Modeling for Short Range Line-of-Sight Terahertz Communication - Tekbiyik, Kursat; Ulusoy, Emre; Ekti, Ali Riza; Yarkan, Serhan; Baykas, Tuncer; Gorcin, Ali; Kurt, Gunes Karabulut (IEEE, 2019)
Underutilized spectrum constitutes a major concern in wireless communications especially in the presence of legacy systems and the prolific need for high-capacity applications as well as consumer expectations. From this perspective, Terahertz frequencies provide a new paradigm shift in wireless communications since they have been left unexplored until recently. Such a vast frequency spectrum region extending all the way up to visible light and beyond points out significant opportunities from dramatic data rates on the order of tens of Gbps to a variety of inherent security and privacy mechanisms, and techniques that are not available in the traditional systems. Thus, in this paper, we investigate statistical parameters for short-range line-of-sight channels of Terahertz communication. Short-range measurement campaign within the interval of [3cm, 20cm] are carried out between 275GHz to 325GHz range. Path loss model is examined for different frequencies and distances to provide the insight regarding the effect of the operating frequency. Measurement results are provided with relevant discussions and future directions.
Keywords: Terahertz channel modeling; short range terahertz communication; THZ COMMUNICATIONS; 300 GHZ; DESIGN; SYSTEM; BAND; Engineering; Telecommunications